O hipogonadismo induzido por de esteroides anabólicos androgênicos é uma condição reversível?: uma revisão sistemática - Vilar Neto, José de Oliveira (2021)
The Anabolic Androgenic Steroids (AAS) are clinically used as an androgen replacement, in hypogonadism treatment, to induce puberty, and also in the treatment of chronic degenerative diseases. The AAS use out of clinical context is becoming massively, being used merely for aesthetic reasons. AAS abuse may cause severe disarrangement on the HPG axis and generate a significant decrease in testosterone synthesis and secretion by the testes. This review aim to evaluate whether the hypogonadism induced by AAS abuse is reversible and under what circumstances the reversibility is possible. For this, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and several databases are used between July and September 2020. Altogether, this systematic review identified and analyzed 179 cases of AAS users. Of these, 168 cases had the hypogonadism clearly diagnosed and proven to be linked exclusively to AAS abuse. However, between these 168 cases, only 38 cases presented fully known outcomes and among these, merely in 4, the hypogonadism was completely reversible (2 based on drug therapy) with HPG axis recovery. In conclusion, this review present evidences that AAS induced hypogonadism is a seriously underestimated problem and in the majority of cases, full recovery is very difficult to succeed.